BROWN SEAWEED (Sargassum ilicifolium) AS A NUTRITIONAL SUPPLEMENT: EFFECTS ON GROWTH AND HEMATOLOGY IN Labeo rohita - Zulfiqar, Rafia; Asad, Farkhanda; Al Sulivany, Basim. S. A.; Naseer, Saba; Kanwal, Irtisha; Nadeem, Aiman; Owais, Muhammad (Science Journal of University of Zakho, 2025)
This experimental trial aimed to evaluate the impact of dietary supplementation with Sargassum ilicifolium on the growth performance and hematology of Labeo rohita. Fingerlings weighing an average of 2.36g were allocated into the control and three treatment groups (3%, 5%, and 7% BSW), each with triplicate (25 fingerlings/aquarium) for 90 days after acclimatized for two weeks. The results indicated that the highest growth rate (P
Keywords: Labeo Rohita; Sargassum Ilicifolium; Growth Performance; Protein Efficiency Ratio; Hematology